The Influence of Social Media on the Effectiveness of Wardah Cosmetic Product Promotions - Maria, Vera; Safana, Nadzwa; Andrayani, Septi; Azahra, Septi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the effectiveness of Wardah product promotion through social media in increasing product sales. Social media makes it easy for a brand to promote and sell its products in a wide range, one of which is the local brand Wardah which is known as